MOOCs and OER: A Model for Library and Information Science Education. Issue 3 (2nd July 2020) - Tsabedze, Vusi wonderboy
Abstract: Eswatini has been sourcing Library and Information Science (LIS) education from foreign institutions due to a shortage of institutions offering LIS training. The relevance of sending officers for training in other countries has been a great concern for the organizations in Eswatini. The complexity of sending officers out of the country for training have caused problem for many organizations due to their absence from the office. As part of the study, a model was designed for implementation of LIS education in Eswatini in the context of Massive Open Online Courses (MOOCs) and Open Educational Resources (OER) platform.